Philosophical and religious aspects of the commodity fetishism (based on the digital economy) - Vorobei, Roman (Skhid, 2026)
This article is devoted to a philosophical and religious analysis of the phenomenon of commodity fetishism in the digital economy. It draws on Georg Simmel's philosophy of money, Karl Marx's concept of commodity fetishism, Max Weber's idea of the “disenchantment of the world,” Mircea Eliade's dichotomy of the sacred and the profane, Walter Benjamin's concept of the “aura” of art, and critical approaches. Max Weber's concept of commodity fetishism, the idea of “disenchantment of the world,” Mircea Eliade's dichotomy of the sacred and the profane, Walter Benjamin's concept of the “aura” of art, as well as the critical approaches of Roland Barthes and Jean Baudrillard to the mythologies of mass culture, this article explores how market relations reproduce the structures of religious consciousness. It is demonstrated that the fetishization of goods in the digital environment is associated with the sacralization of value, which is based on a collective belief in the “magical” power of money, brands, and digital objects. Particular attention is paid to NFTs as a prime example of a digital fetish that combines economic, cultural, and quasi-religious dimensions. It is demonstrated that in 2020–2021, NFTs functioned as an economic, cultural, and technological fetish. Digital code and artificial scarcity endowed tokens with an “aura” of uniqueness and the promise of belonging to elite communities. At the same time, mass replication, speculative expectations, and imitation practices of cargo cult induced oversupply and a crisis of trust. Declining trade volumes and a sharp drop in prices demonstrate the process of demythologization. The magical status of the token is fading, and NFTs are returning to the status of an ordinary risky asset.